Comparing mixed reality use in ecologically distinct urban sites: embodied tools for participatory environmental design - Karabagli, Kaan; Gurer, Ethem (Frontiers in Virtual Reality, 2025)
Mixed reality (MR) environments offer new opportunities for embodied interaction in participatory design processes. This study evaluates whether mobile MR tools influence ecological awareness and co-design behavior across two distinct urban settings. Twenty participants from architecture and design disciplines took part in structured workshops involving MR-supported design tasks. Sessions were conducted in a spatially bounded university courtyard and on a semi-natural coastal island. Both sites were selected for their differing environmental characteristics, allowing a comparative assessment of MR’s effectiveness under varied ecological conditions. Participants used mobile augmented reality interfaces to visualize and situate ecological design proposals, including tree-based structures, habitat-supportive elements, and spatial overlays oriented toward nonhuman actors. Observational logs, post-session surveys, and coded design artifacts were used to evaluate behavior. Ninety percent of island participants and seventy percent of courtyard participants integrated ecological elements into their final designs. Reflections revealed more frequent references to nonhuman spatial actors among island participants. Reported cognitive fatigue and difficulty using the MR interface were higher in the island group, with 60 percent citing spatial or interface overload. Half of the participants also expressed uncertainty about authorship and the persistence of their digital contributions. These findings suggest that MR interfaces can support multispecies engagement and participatory ecological design, but their effectiveness depends on the sensory density, narrative framing, and infrastructural legibility of the spatial context. The results provide preliminary evidence that MR can function as a perceptual and participatory tool for inclusive environmental design under specific spatial and cognitive conditions.